Urotensin-II gene rs228648 polymorphism associated with the risk of diabetes mellitus. Issue 6 (7th December 2018) - Zhao, Yawei; Fang, Shuhua; Que, Kerong; Xu, Guangli; Zhang, Heng; Qi, Cong; Yang, Nian
Abstract : Background : Urotensin-II (UII) rs228648 polymorphism has been reported to be associated with the risk of diabetes mellitus (DM) with inconsistent results. The present study sought to reassess the relationship between this polymorphism and susceptibility to DM by meta-analysis. Methods : Relevant eligible studies and whole genome association study (GWAS) data electronically searched were pooled to evaluate the strength of the association with odds ratios (ORs) and 95% confidence intervals (CIs). Results : Seven case–control studies involving 894 cases and 1186 controls were finally included in the meta-analysis. Overall analyses indicated that UII gene rs228648 variant was significantly associated with reduced risk of DM (allele, A vs. G: OR = 0.68, 95%CI = 0.56–0.82; dominant, AA+GA vs. GG: OR = 0.70, 95%CI = 0.53–0.91; homozygote, AA vs. GG: OR = 0.41, 95%CI = 0.28–0.61; recessive, AA vs. GA+GG: OR = 0.36, 95%CI = 0.19–0.71). In subgroup analyses based on ethnicity, the results showed a significant association of rs228648 polymorphism with decreased risk of DM in Chinese population under all five genetic models as well as in non-Chinese population under heterozygote and recessive models. Stratified analyses by specific type of DM also presented a significant association for common diabetes mellitus (CDM) under allele and homozygote as well as gestational diabetes mellitus (GDM) under all genetic models except for homozygote model. However, the synthetic analysis with GWAS data suggested an increased risk of DM with rs228648 effect allele in European population (OR = 1.01, 95%CI = 1.00–1.02). Conclusion : The present meta-analysis preliminarily suggested a potentially opposite role of rs228648 polymorphism associated with DM risk in the Chinese and European population. Further studies are in great request to verify the results.